Structure of the Ring Cleavage Product of 1-Hydroxy-2-Naphthoate, an Intermediate of the Phenanthrene-Degradative Pathway of Nocardioides sp. Strain KP7 - Adachi, Kyoko (American Society for Microbiology, 1999)
1-Hydroxy-2-naphthoate (compound I) is a metabolite of the phenanthrene-degradative pathway in Nocardioides sp. strain KP7. This singly hydroxylated aromatic compound is cleaved by 1-hydroxy-2-naphthoate dioxygenase. In this study, the structure of the ring cleavage product generated by the action of homogeneous 1-hydroxy-2-naphthoate dioxygenase was determined upon separation by high-performance liquid chromatography at pH 2.5 by using nuclear magnetic resonance (NMR) and mass spectroscopic techniques. The ring cleavage product at this pH existed in equilibrium between two forms, 2-oxo-3-(3-oxo-1,3-dihydro-1-isobenzofuranyl)propanoate (compound III) and 2,2-dihydroxy-3-(3-oxo-1,3-dihydro-1-isobenzofuranyl)propanoate (compound IV). After the pH of the solution was raised to 7.5, the structure of the major species became (E)-4-(2-carboxylatophenyl)-2-oxo-3-butenoate (compound II; common name, trans-2′-carboxybenzalpyruvate), which was in equilibrium with compound III. Direct monitoring of the enzymatic formation of the ring cleavage product by (1)H-NMR in a deuterated potassium phosphate buffer (pH 7.5) detected only compound II as a product, and the proton on carbon 3 of compound II was not exchanged with deuterium. Thus, compound II is likely to be the first stable product of dioxygenation of 1-hydroxy-2-naphthoate.